Participatory Decision Making in Educational Organisations: Review of Instruments - Mehta , Deepa; Gardia , Alok (INDIAN EDUCATIONAL REVIEW, 2009)
Participatory Decision Making (PDM) in educational organisations has been studied extensively by Scholars. Current theorists maintain that teacher participation in decision making not only facilitates decision implementation, but leads teachers to feel respected and empowered. This point of view derives support from the ‘human relations’ school of thought too. In spite of the overall importance of teacher’s participation in decision making the major problem faced by the researchers in educational management today, is of selecting appropriate measuring instrument to quantify PDM, and the problem may be due to lack of a uniformally accepted multi-dimensional construct. Present article reviews the available instruments on PDM from India and abroad. The article provides conceptual development of PDM in view of its measurement and its dimensions identified in various previous studies. Further, the article also advocates multi-dimensionality of the instrument on the basis of previous researches and reports all available decision areas where teacher’s empowerment may lead the organisations to perfection in all the dimensions of organisational effectiveness.